Pengaruh Profit Margin Pembiayaan Murabaḥah Terhadap Profitabilitas BPRS Bhakti Sumekar - Herlita Merina; Wardatus Syarifah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The Indonesian banking system adopts a dual banking system, consisting of conventional and Islamic banking. Islamic banking emerges as an alternative free from interest (riba), emphasizing Islamic principles in financial transactions, such as financing based on the murābaḥah contract. One financial institution implementing this system is BPRS Bhakti Sumekar. Murābaḥah has become one of the most in-demand products, increasing annually and showing a significant contribution to the bank's operations. However, the increase in murābaḥah financing does not always align with rising profitability, which in this study is measured by Return on Assets (ROA). Based on financial reports from 2015 to 2021, murābaḥah financing tends to increase, while ROA fluctuates and tends to decline. This phenomenon raises questions about the effectiveness of the murābaḥah profit margin in improving the profitability of Islamic banks.. This study uses a descriptive quantitative method. The population includes the financial reports of PT. BPRS Bhakti Sumekar from 2018 to 2023. The sampling technique used is non-probability sampling, which gives each population member a chance to be selected as a sample. The data were analyzed using classical assumption tests and hypothesis testing. The results show that the murābaḥah financing profit margin does not significantly affect profitability (ROA), with a t-count value of -1.700, which is smaller than the t-table value of 2.064. The coefficient of determination (R square) is 0.116, indicating that the murābaḥah profit margin only contributes 11.6% to the profitability variable, while the remaining 88.4% is influenced by other variables not included in this study.